Les dimensions des interventions organisationnelles de maintien du lien d’emploi des travailleurs victimes de lésions professionnelles - Diane Berthelette; Raymond Baril (Perspectives Interdisciplinaires sur le Travail et la Santé)
In this paper, we present the conceptual framework of an intervention designed to facilitate the return to work of workers suffering from occupational injuries. The intervention in question is in fact a policy designed by the Quebec workplace health and safety commission. The first phase of the research consisted in a content analysis of prescriptive and scientific publications on early return to work interventions. It was followed by case studies involving interviews with employer and worker representatives in 16 private firms.The paper describes the normative theory of the early RTW intervention, more specifically the aspects of its structure and process and the mechanisms by which interventions of this nature are expected to produce their outcomes. The structure includes the composition of the RTW team along with the following services and activities : team co-ordination, information given to workers, communication between the firm and the worker’s physician, medical validation, job assignment, work organization, firm/worker relations, remuneration, support in finding employment outside the firm, and program evaluation.Our results are useful in optimizing the content validity of instruments that may be developed to measure the implementation of early RTW interventions. In addition, they will be useful for staff members or researchers wishing to produce a logical analysis of such interventions.